Factors Influencing Smoking Initiation among School-Age Children and Adolescents in a Malay Settlement Village: A Cross-Sectional Study - Nor Aini Abdullah; Muhammad Iqbal Hafi Nor -Aizuddin; Muhammad Nabil Mohd Nahzan; Fatin Nabila Mohd Kassim; Tengku Nur Iffah Tengku Fadil Hisham; Nur Aishah Abd Ghani; Ain Najmin Norhaizan; Ainul Fatihah Mohd Saidi; Siti Zaitun Che Hassan; Auni Muyassarah Kamaluddin; Hairul Izwan Abdul Rahman; Sabaridah Ismail (Asian Journal of Medicine & Health Sciences, 2023)
Smoking initiation among children and adolescents is a pressing global health concern. This study investigates the prevalence and factors influencing smoking initiation among school-age children and adolescents in a Malay settlement village. The research utilized a cross-sectional design and collected data from all school-going children and adolescents aged 7 to 17 in a Malay settlement village through face-to-face interviews. Smoking was defined as currently using cigarettes, vapes or both. Predictor variables were assessed using the univariate analysis followed by multivariate logistic regression analysis. Out of 187 respondents, a total of 33.7% were identified as smokers. The study revealed that peer pressure (aOR=7.0, 95% CI [2.49, 19.83]), parental permission to smoke (aOR=3.9, 95% CI [1.10, 13.88]), adults frequently asking children to buy cigarettes (aOR=3.9, 95% CI[1.68, 9.07] ), and having siblings who smoke (aOR=2.7, 95% CI[1.11, 6.61]) were significant factors influencing smoking initiation. Peer influence was the most significant factor among male participants (aOR=9.3, 95% CI [2.58, 33.70]). Peer influence was found to be the most significant factor, increasing the likelihood of starting to smoke nearly seven times among all participants, and almost nine times among male participants alone when peer influence was present. Family factors, such as sibling smokers, no parental restriction and adults asking children to buy cigarettes, were among the significant factors. This study recommends stricter regulations on retailers selling cigarettes and vapes to school-aged children, preventing adults from involving children in cigarette purchases, and utilizing peer influence for targeted health education.